The Effect of Short Story Extensive-Reading on EFL Reading Attitudes of the Secondary School Student - Nita, Nita; Susilo, Susilo; Surya, Satyawati (Universitas Nusantara PGRI Kediri, 2022)
This study intends to investigate the effect of short story extensive reading on secondary school students’ EFL reading attitudes. This is an experimental study using a one-grouppretest-treatment-posttest design. The sample was 35 students, who were taken randomly from 355 Students of twelve classes in the second grade of SMAN 4 Samarinda. The researchers used a questionnaire as the instrument in this study. The questionnaire was used to obtain the data on students’ reading attitudes. To analyze the data, a series of paired t-tests and descriptive statistics were used. The results revealed that firstly, overall aspect, the short story-extensive reading gave an effect on the EFL secondary school students’ reading attitudes, t (34)= -1.229, p=0.003. Secondly, in detail per an aspect of attitude, the short story-extensive reading gave an effect on the comfort aspect in the students’ reading attitudes, t (34)= -3.610, p=0.001, the linguistic value aspect, t (34)= 0.463, p=0.646, and the anxiety aspect, t (34)= -3.762, p=0.001; In the meantime, the short story-extensive reading did not give an effect on the intellectual value aspect in the students’ reading attitudes, t (34)= -0.269, p=0.789 and the practical value aspect, t (34)= -0.179, p=0.859. Reading short stories brings about the students into a relaxed circumstance from which EFL secondary school students can browse ideas freely and excitingly. This study implies that such reading materials can be used by secondary school EFL teachers to give more reading input-rich circumstances, which finally becomes an enhancement of their reading attitudes. Keywords:EFL Reading attitude, Secondary school student, E-short story extensive-reading